Background of Double Tee Construction and Need for Standardized Precast Double Tee for Indian Building Industry - et. al., G. Phani Ram, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The small scale residential and commercial office spaces in India are mostly engineered and built using reinforced concrete cast-in-place design and construction methods. Even though precast concrete engineering and design methods are well developed and practiced in advanced countries, the same has not happened in India. Though some major projects in metropolitan cities have been completed in precast engineering and construction, precast concrete engineering is still very premature for small scale residential and commercial infrastructure. Although factors such as centuries-old practice, availability of inexpensive labor have been primary causes for cast-in-place concrete construction, lack of technology and research outcome reach, unavailability of standard products and methods, inadequate shipping and handling capabilities that require reliable transportation infrastructure also weigh in towards cast-in-place construction as opposed to precast construction. This research started with the primary objective of identifying and developing standard precast double tee concrete beam-slab members for Indian market. Precast double tee concrete members (often called as DT) are very standard flooring and roofing options in advanced countries. These members can offer very viable concrete flooring and roofing solution to most of the residential and small office spaces in India. However, the member designs for Indian market will be significantly different from standard designs seen elsewhere in other countries. Manufacturing capabilities, shipping capacities, crane handling limitations, truck sizes and highway transportation constraints being so different from advanced countries, demand for standard geometry and design that fits local needs. In the first part of this research, a thorough background of PCI standard DT member showing its geometry and standard design is given. An introduction to PCI load tables is done showing examples on its application. After that a market survey has been conducted to understand the design and construction practices of precast double tee members supplied by some of the Indian precasters. An effort has been made to capture the preferences such as span of the members, fully precast versus partial precast with field topping, thickness of topping slab, and prestressing strand size. Also, the survey questions tried to identify shipping and handling limitations due to transportation restrictions. Finally, the results are analyzed and trends are presented. Effort is made to learn the precast practices in Indian market. It is found that there is no standardized double tee member design available for Indian precast market. It is concluded that the idea of developing standard DT member for Indian precast segment will be a very useful contribution and encourages the authors to continue with developing standard design for typical precast prestressed DT members for small scale residential and commercial structures in India